Pan‐Arctic Distribution of Bioavailable Dissolved Organic Matter and Linkages With Productivity in Ocean Margins. Issue 3 (2nd February 2018) - Shen, Yuan; Benner, Ronald; Kaiser, Karl; Fichot, Cédric G.; Whitledge, Terry E.
Abstract: Rapid environmental changes in the Arctic Ocean affect plankton productivity and the bioavailability of dissolved organic matter (DOM) that supports microbial food webs. We report concentrations of dissolved organic carbon (DOC) and yields of amino acids (indicators of labile DOM) in surface waters across major Arctic margins. Concentrations of DOC and bioavailability of DOM showed large pan‐Arctic variability that corresponded to varying hydrological conditions and ecosystem productivity, respectively. Widespread hot spots of labile DOM were observed over productive inflow shelves (Chukchi and Barents Seas), in contrast to oligotrophic interior margins (Kara, Laptev, East Siberian, and Beaufort Seas). Amino acid yields in outflow gateways (Canadian Archipelago and Baffin Bay) indicated the prevalence of semilabile DOM in sea ice covered regions and sporadic production of labile DOM in ice‐free waters. Comparing these observations with surface circulation patterns indicated varying shelf subsidies of bioavailable DOM to Arctic deep basins. Key Points: The prevalence of bioavailable DOM reflects ecosystem productivity in Arctic margins Hot spots of labile DOM are widely distributed during summer in the Chukchi Sea Shelf regions are important sources of bioavailable DOM for microbial food webs in the central basins